Library as a social cluster information support - O. Yu. Murashko (Библиосфера)
The article analyzes modern library capability as a social cluster information support. A social cluster information support is offered to be considered not only as technological processes, but also as a process of intellectual resources exchange, that promotes recognition of a library as a territorial center of information-technological resources.